Further evidence for deletions in 7p14.1 contributing to nonsyndromic cleft lip with or without cleft palate. Issue 9 (7th July 2016) - Klamt, Johanna; Hofmann, Andrea; Böhmer, Anne C.; Hoebel, Ann‐Kathrin; Gölz, Lina; Becker, Jessica; Zink, Alexander M.; Draaken, Markus; Hemprich, Alexander; Scheer, Martin; Schmidt, Gül; Martini, Markus; et al.
Abstract : Background: Nonsyndromic cleft with or without cleft palate (nsCL/P) is a common birth defect. Although genome‐wide association studies (GWAS) have identified numerous risk variants, a considerable fraction of the genetic heritability remains unknown. The aim of the present study was to replicate a previous finding that de novo deletions in a 62 kb region of chromosome 7p14 are a risk factor for nsCL/P, using an independent cohort. Methods: Data from a published case–control GWAS cohort of 399 patients and 1318 controls were used. Copy number variant (CNV) detection in the 62 kb candidate region of 7p14 was performed using QuantiSNP. Putative CNVs in probands were verified and validated by quantitative polymerase chain reaction. Segregation analyses were performed in family members for whom DNA was available. Results: Within the 62 kb candidate region, a deletion of 7.4 kb showed association with nsCL/P (13/387 cases, 20/1300 controls, p lowest = 0.024, odds ratio = 2.22). In all families with a sporadic case ( n = 3), the deletion occurred de novo . In multiplex families, both incomplete segregation and incomplete penetrance were observed. Conclusion: The present data support the hypothesis that deletions at 7p14 are a common risk factor for nsCL/P. Genome‐wide CNV analyses in nsCL/P cohorts are warranted to explore the functional relevance of these deletions and their contribution to nsCL/P, and to determine exact breakpoints. Birth Defects Research (Part A) 106:767–772, 2016. © 2016 Wiley Periodicals, Inc.